Impact of new undercrossing tunnel excavation on the stability of the existing tunnel - Zhu, Qingli; Ding, Yanping (Frontiers in Earth Science, 2022)
The rapidly expanding transportation hub system in China has driven a large number of track and highway engineering projects nationwide, resulting in increasing interchanges of highway and railway tunnels year on year. The mutual impact between new and existing tunnels is one of the most important topics in geotechnical engineering. Constructed undercrossing, an existing highway tunnel is commonly seen in new railway tunnel projects. The new railway tunnel excavation will affect the stability and safety of the existing highway tunnel. Our study takes the newly built Huilongwan Railway Tunnel section undercrossing the existing Longzhouwan Highway Tunnel, one of the East Ring Line Projects of Chongqing Railway Terminal, as the object. This article simulated the displacement changes and structural deformation pattern of the existing highway tunnel caused by the excavation of the new railway tunnel with finite element analysis software and compared them with on-site measurements one by one to clarify the impact of new railway tunnel excavation on the stability of the existing highway tunnel. The result proved that the non-blasting excavation with a three-step temporary invert method could ensure the safety of the existing highway tunnel.